From Nationalism to National Indifference: Binary Logic and Sense of Time. Issue 5 (26th September 2021) - Lieberman, Benjamin
Abstract: The vast body of inquiry into nationalism has traditionally seen Europe as a main center for the emergence of nationalism, but scholars of "national indifference" have countered with the idea that nationalism may not matter much at all as a motive for most people. The concept of national indifference calls into question the power of nationalism as a motive for action and the mass appeal of nationalism. Studies of national indifference have constructed an alternative non-national narrative, but face particular challenges accounting for major themes and episodes of discrimination and violence. At its core, national indifference paradoxically both rejects and accepts binary notions of identity and incorporates binary assumptions about motives. It is tempting to resolve the contest between parallel accounts of pervasive, powerful nationalism and national indifference by choosing a victor, but this contrast between models shows the fluidity and dynamism of nationalism. The debate between the now classic accounts of nationalism and the alternative of national indifference points to the importance of often overlooked variables: frames and sense of time.